Kejadian Pasien drop out dari Rencana Pelayanan Rehabilitasi Medik Rumkital di RSAL Dr. Ramelan - LENA WIJAYANINGRUM; HERIN SETIANINGSIH; SETIYONO (HANG TUAH MEDICAL JOURNAL, 2021)
ABSTRACT Background : The high number of patient visits to medical rehabilitation clinic, from January to June 2018 is 13.772 patients, the number of patients from July to December 2018 is 11.142 patients, and the number of patients from januari to july 2019 is 13.781 patients.Therefore it is important to know the continuity of service, as planned by medical rehabilitation specialist. Methode : Descriptive research with population was obtained in medical record for duration 1 December 2019 to 29 February 2020 in the medical rehabilitation clinic of Dr Ramelan Surabaya Result : Patient visits that dropped out in 3 months were 795 patients (less than 10 visit in 3 months ). Patient visits that did not drop out in 3 months were 194 patients more than or equal to 10 visits in 3 months Conclusion : The incidence of patient drop out for planned rehabilitation services is 80,3842%. So the incidence of patient drop-out for planned rehabilitation services is not meeting the standards